Health seeking behaviors of nurses diagnosed with hypertension and providing health care in resource-constrained setting in a rural part of Northern Ghana: A qualitative study - Thomas Ankomanin; Kennedy Dodam Konlan; Kwadwo Ameyaw Korsah (PLoS ONE, 2026)
Background Hypertension poses a significant occupational health threat to nurses globally, exacerbated by demanding work environments that can hinder their own health-seeking behaviors. In Ghana, despite a high burden of non-communicable diseases and the existence of employee health and wellbeing programme, evidence on how nurses with hypertension navigate their personal health management remains limited, particularly in high-stress settings like those in rural part of Ghana. Aim We explored the health seeking behaviors of nurses diagnosed with hypertension and providing health care in a resource-constrained setting in a rural part of Northern Ghana. Methods The study employed a qualitative, exploratory-descriptive design. Through purposive sampling, twelve (12) nurses diagnosed with hypertension were recruited from the Kintampo Municipal Hospital’s Employee Wellness Clinic. Data was collected via in-depth, semi-structured interviews which were audio-taped and transcribed verbatim. Thematic analysis, guided by Braun and Clarke’s framework and supported by NVivo 14.0 software, was used to assist with the data analysis. Results The analysis yielded nine major themes. The participants demonstrated high biomedical knowledge and perceived hypertension as a severe condition, strongly linked to occupational stress. Key barriers to effective management included overwhelming workload and scheduling constraints, financial limitations, a pervasive culture of professional self-reliance and stigma, and a critical lack of institutional support systems. While family and peer support were vital facilitators, they were insufficient to overcome systemic barriers. Nurses exhibited strong self-management practices, but their health-seeking was often reactive rather than preventive. Conclusion and recommendations A significant gap exists between nurses’ knowledge of hypertension and their health-seeking actions. This gap is primarily driven by organizational and systemic barriers within the workplace, rather than a lack of individual awareness. To protect this critical workforce, we recommend that nurse managers, hospital management and health policymakers must prioritize the implementation of structured, low-cost workplace wellness programmes. These should include routine screening, flexible scheduling, anti-stigma campaigns to promote health-seeking, and confidential peer support systems to enable nurses to translate their knowledge into consistent self-care practices when diagnosed with hypertension.